2006
DOI: 10.1089/jwh.2006.15.251
|View full text |Cite
|
Sign up to set email alerts
|

The Causes and Consequences of Overactive Bladder

Abstract: Overactive bladder (OAB) is a syndrome characterized by symptoms of urinary urgency with or without urgency urinary incontinence (UUI), usually with frequency and nocturia. OAB affects approximately 17% of women in the United States and Europe. The causes of OAB, as with many bladder disorders, are multifactorial and are not completely understood. The primary functions of the lower urinary tract (bladder and bladder outlet mechanism) are storage and evacuation of urine. The bladder and the micturition cycle ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Although the pathophysiology of OAB is not fully understood, either neurogenic or myogenic dysfunction can produce OAB symptoms (Miller and Hoffman, 2006). Recent studies showed that activation of β3-AR caused relaxation of the detrusor muscle during bladder filling.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathophysiology of OAB is not fully understood, either neurogenic or myogenic dysfunction can produce OAB symptoms (Miller and Hoffman, 2006). Recent studies showed that activation of β3-AR caused relaxation of the detrusor muscle during bladder filling.…”
Section: Discussionmentioning
confidence: 99%
“…As soon as the woman feels wetting herself due to escape of urine, being embarrassed, reactive sympathetic activity reflex, will increase the sympathetic tone at the IUS to confirm its closure and preventing further leak of urine. This may explain the strong indications that there is a causal relationship between OAB and POP (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Thus by understanding this new concept, we can explain most of the voiding troubles.…”
Section: Second Stage Of Micturition: (Figure 1) 2mentioning
confidence: 95%
“…The pathophysiology and etiology of OAB currently remain unknown (Miller and Hoffman, 2006;Wein and Rackley, 2006). About 33 million adults suffer from OAB in the United States (Coyne et al, 2011).…”
Section: Introductionmentioning
confidence: 99%